INFLUENCE OF SCHOOLS' DEMOCRATIC LEADERSHIP PRACTICES ON STUDENTS' PARTICIPATORY DECISION MAKING IN PUBLIC SECONDARY SCHOOLS IN TIGANIA EAST SUB COUNTY, MERU COUNTY, KENYA - Mburuki, Lawrence; Thinguri, Ruth (African Journal of Education and Practice, 2022)
Purpose: Globally, there is a concern on the way learners are being involved in decision making in their schools. The purpose of this study was to investigate the influence of schools' democratic leadership practices on students' participatory decision making in public secondary schools in Tigania East Sub County, Kenya. Methodology: This study was guided by the Participative Leadership Theory and the Normative Decision-making Theory. The study embraced mixed methodology and the concurrent triangulation with descriptive survey for quantitative data design. The target population was 479 which included: 25 principals, 250 teachers, 4 education officers and 200 students. The total sample was 199 participants. This included 11 principals, 110 teachers, 4 education officers and 74 student leaders. There were questionnaires for teachers and interview schedule for principals. The instruments were piloted in Tigania Central Sub County using 10 teachers and 6 BoM chairpersons representing 10% of the total sample. The piloting participants was not included in the final sample since they came from another sub county. Quantitative data was analyzed in descriptive and presented using tables, frequencies and percentages. Qualitative data was analyzed through thematic analysis presented in narrative form and verbatim citations. Findings: The study established that schools' democratic leadership practices as independent variables were fully fulfilled and students' participatory decision making was present among schools in the study area. It was recommended that more research be done in Meru using various participants and the government establish if students participated fully in decision making processes. Unique Contribution to Theory, Policy and Practice: Participative Leadership Theory emphasizes participation in making decisions. It is quite democratic in nature. It emphasizes team members making decisions. Normative Decision-Making Theory shows the effectiveness of the decision-making process measures. The theories were validated as they showed participation and effective decision making. It was recommended that more research be done in the study area on the same subject.